Physico-Mechanical Properties of Almond Nut and Its Kernel as a Function of Variety and Moisture Content - Arslan, Selcuk; Vursavus, Kubilay K. (2008)
The physical and mechanical properties of three almond nut varieties (Ferragnes, Ferradual and Guara) were determined. Significant differences were found among the varieties in terms of principal dimensions (length, width and thickness), geometric mean diameter, sphericity, surface area, volume and mass for nut and kernel. The effect of moisture content and compression axis on rupture force, deformation, energy absorbed and power requirement for Ferragnes variety was investigated. The tests were carried out at four moisture contents [6.16, 11.67, 19.21 and 26.79% (d.b.)] and at three compression axes (vertical, horizontal and thickness) to measure the nut shell resistance. Generally, rupture force, deformation, energy absorbed and power requirement decreased with an increase in the moisture content for all compression axes. This decrease continued until moisture content of 26.79% (d.b.) along the thickness axis for deformation and power requirement. According to the results of variety differences at a single moisture content of 6.16% (d.b.), Ferragnes had the highest kernel rupture force, energy absorbed and power requirement at a deformation rate of 0.133 mm s-1 along the horizontal axis. Further, Guara variety had the highest values for all mechanical properties of nut shell.
Keywords: Nuts; Kernel Functions